Strategy for Development of Ground Coffee Business Production in Kaongkeongkea Village, Pasarwajo District, Buton Regency (Case Study Anes Coffee) - Antasalam Ajo; Wa Ode Dian Purnamasari; Haristiawan H (AIQU: Journal Multidiscipliner of Science, 2023)
This research aims to find out the best strategy for developing a ground coffee business in Kaongkeongkea Village, Pasarwajo District, Buton Regency. This research was carried out from June to July 2022. This research involved 3 respondents, 1 business leader and 2 production employees. Research data was obtained from interviews, filling out questionnaires and observations. The method used is SWOT analysis. From the results of research conducted regarding the Strategy for developing Ground Coffee Production, the most appropriate strategy that can be used in Ground Coffee Development is an Aggressive Strategy by utilizing S-O: Improving the quality of ground coffee products by optimizing the use of facilities and infrastructure in the production process. Meanwhile, the supporting strategy that can be utilized is the W-O strategy: Making more use of infrastructure in the production process in order to increase the amount of production. S-T Strategy: Create innovative ground coffee product variants and collaborate with products from other regions. W-T Strategy: Looking for investors to collaborate in processing the production of ground coffee business.